2006
DOI: 10.1590/s0004-282x2006000500008
|View full text |Cite
|
Sign up to set email alerts
|

Structural brain abnormalities in early-onset schizophrenia

Abstract: -Background: Few studies investigated brain abnormalities in early onset schizophrenia. Objective: To assess computed tomography (CT) abnormalities in patients with childhood or adolescence onset schizophrenia. Method: CT scans of patients with childhood (6 to 11 years old) (N=6) or adolescence (12-17 years old) (N=9) schizophrenia were compared to normal controls. Patients were diagnosed based on the DSM-III-R criteria. Ventricular enlargement was measured by the Ventricle to Brain Ratio (VBR) and Cortical At… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Indeed, ketamine-induced release of glutamate in anterior cingulated cortex (ACC) is correlated with positive psychotic symptom scores in healthy human subjects ( r = 0.72) (Stone et al, 2012). Furthermore, NMDAR antagonists play known roles in neurodegenration and excitotoxicity, including apoptosis of mature corticolimbic pyramidal cells (Zhou et al, 2007; Farber and Olney, 2003; Horváth et al, 1997; Wozniak et al, 1998), thus offering NMDAR hypofunction as a possible basis for brain atrophy observed in schizophrenia (Rais et al, 2012; Andreone, et al, 2007; Rais et al, 2008; Goldman et al, 2007; Ferrari et al, 2006). …”
Section: Evidence For Nmdar Dysfunctionmentioning
confidence: 99%
“…Indeed, ketamine-induced release of glutamate in anterior cingulated cortex (ACC) is correlated with positive psychotic symptom scores in healthy human subjects ( r = 0.72) (Stone et al, 2012). Furthermore, NMDAR antagonists play known roles in neurodegenration and excitotoxicity, including apoptosis of mature corticolimbic pyramidal cells (Zhou et al, 2007; Farber and Olney, 2003; Horváth et al, 1997; Wozniak et al, 1998), thus offering NMDAR hypofunction as a possible basis for brain atrophy observed in schizophrenia (Rais et al, 2012; Andreone, et al, 2007; Rais et al, 2008; Goldman et al, 2007; Ferrari et al, 2006). …”
Section: Evidence For Nmdar Dysfunctionmentioning
confidence: 99%
“…Age-related changes in brain structure result from a complex interplay among various neurobiological processes, which may contribute to more complex trajectories than what can be described by simple linear or quadratic models [14,15].…”
Section: Discussionmentioning
confidence: 99%
“…Volumetric magnetic resonance imaging (MRI) studies of patients with schizophrenia have demonstrated an overall reduction in grey matter; an increase in white matter; decreased size of the amygdala, hippocampus, and parahippocampus; an overall reduction in brain volume; and larger lateral ventricles relative to a control group. [35][36][37] …”
Section: Patient Symptoms and Schizophreniamentioning
confidence: 99%